2011
DOI: 10.3139/217.2381
|View full text |Cite
|
Sign up to set email alerts
|

Elastomer Nanocomposites Based on NR/EPDM/Organoclay: Morphology and Properties

Abstract: Natural rubber/Ethylene Propylene Diene Monomer (NR/ EPDM) blends of five different compositions (0/100), (25/75), (50/50), (75/25) and (100/0) with 1, 3, 5 and 7 phr organo-modified nanoclay (Cloisite 15A) were prepared by two-roll mill. The effect of organo-modified layered nanosilicates and composition on the cure characteristics, microstructure, mechanical, and rheological properties of the nanocomposites were studied. Results suggested the intercalation of polymer chains into the silicate layers which was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
87
0
3

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 64 publications
(94 citation statements)
references
References 33 publications
4
87
0
3
Order By: Relevance
“…As seen the fractured surface of pristine NR/BR (Fig 3-a) is smooth. The harsh surface of NR/BR filled compound by 7wt% nanoclay (Fig 3-b) exemplifies an effective interaction established between polymer matrix / filler [2], [15]. The SEM photomicrographs shown in Figure 6 confirm that smaller particle size of the filler provides a larger surface area for a better filler dispersion and interfacial bond between filler and rubber matrix.…”
Section: B Sem Resultsmentioning
confidence: 59%
See 4 more Smart Citations
“…As seen the fractured surface of pristine NR/BR (Fig 3-a) is smooth. The harsh surface of NR/BR filled compound by 7wt% nanoclay (Fig 3-b) exemplifies an effective interaction established between polymer matrix / filler [2], [15]. The SEM photomicrographs shown in Figure 6 confirm that smaller particle size of the filler provides a larger surface area for a better filler dispersion and interfacial bond between filler and rubber matrix.…”
Section: B Sem Resultsmentioning
confidence: 59%
“…Shift of the organoclay diffraction peak to lower 2θ values indicated that elastomer chains intercalated between consequent silicate layers. This clearly indicates that inter lamellar spacing of the clay are enlarged after melt compounding [2]. Moreover, XRD results of different compositions of NR/BR containing 5 wt% is shown in Fig 2. As can been seen, as the BR content of the samples increases, the organoclay diffraction peak shifts toward lower angles and consequently, the peak intensity declines.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations